MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VIII PADA MATERI GELOMBANG DAN ALAT OPTIK DENGAN MODEL DISCOVERY LEARNING - Naurah Nazifah; Nurul Izzah; Elvi Suryanti; Siti Asma Hanum (Universitas Sriwijaya, 2022)
This study aims to describe the increase in learning motivation and cognitive learning outcomes of students. This research is a classroom action research. The research subjects were all eighth grade students of SMP N 1 Payakumbuh which gathered 34 students. The results of this study indicate that the initial motivation obtained an average score of 61.59 which is in the low category. While the average final motivation after the application of the discovery learning model obtained an average score of 70.68 in the high category. Cognitive learning outcomes of students in the first cycle obtained an average value of student learning outcomes in the knowledge aspect of 77.12 with a classical mastery percentage of 76% for wave material. In the second cycle, the average score of students increased to 81.97, the percentage of completeness was 85% for the optical instrument material. Based on the results of the study said that the application of Discovery Learning learning model can increase learning motivation students and student cognitive learning outcomes.